Growth of intact plants and coppice in short rotation eucalypt plantations - Souza, Felippe Coelho de; Reis, Geraldo Gonçalves dos; Reis, Maria das Graças Ferreira; Leite, Helio Garcia; Faria, Ronan Soares de; Caliman, Jônio Pizzol; Barbosa, Rodolfo Alves Barbosa; Oliveira, Carlos Henrique Rodrigues de (New Forests, 2015)
The growth of intact plants and coppice of juvenile plants of eight eucalypt clones (3 × 3 m spacing) was evaluated in the savanna region, Brazil (17°36′09″S and 46°42′02″W), aiming for biomass production for energy in short rotations. The treatments included intact plants and juvenile plant coppice (cut at 13 months of age). Coppice was managed either with thinning to two sprouts/stump at 9 months after harvesting or without sprout thinning. The diameter of the intact plants was greater than that of coppice for clones 58, GG100, 26 and 8B, and no differences were noted between treatments for the other clones. Yield did not differ between the thinned and unthinned sprouts for most clones. At younger ages, the coppice yield was greater than that of the intact plants for most clones. Later, there was a decline in the coppice yield, and intact plants surpassed coppice. Then, the maximum coppice mean annual increment was achieved at younger ages than for the intact plants, which resulted in coppice rotation age shortening. The greatest differences between the coppice and intact plants yield was between 38 and 40 months, when the coppice yield was 59, 56, 127, 149 and 75 % greater than that of the intact plants, for the clones 58, GG100, 1000, 36 and 910, respectively. Clone GG100 revealed the highest yield estimation among the intact and coppice plants. The results indicate that by coppicing juvenile eucalypt clone plants, in dense stands, it is possible to produce biomass for energy, without sprout thinning, if rotation age is shortened.
Keywords: Juvenile plant coppice; Biomass for energy; Sprout thinning; Eucalypt short rotation